2002
DOI: 10.1086/340499
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Sources and Star Formation Activity in the Sagittarius B2 Cloud Observed withChandra

Abstract: We report the X-ray population study in the giant molecular cloud Sagittarius B2 (Sgr B2). More than a dozen X-ray cloud members (and candidates) are discovered with Chandra. Two bright X-ray sources are located near Sgr B2 Main, the most copious complex of the ultracompact H ii sources. The X-ray spectra are fitted with a thin thermal plasma model of 5-10 keV temperature. The intrinsic luminosity, after correcting the absorption of~5 Â 10 23 H cm À2 , is $10 33 ergs s À1 . Although these two X-ray sources are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…To calculate the 99 per cent confidence level MDP of the medium/hard X-ray instrument (see Marin et al 2012b Sidoli et al 2001;Terrier et al 2010) being close to the one of the Crab ( ∼ 2), in first approximation we can assume similar fluxes (in mCrab) in the MEP energy band if we neglect absorption below 8 keV. No observation of Sgr C has been made above 10 keV yet, but its soft X-ray continuum has been fitted with a ∼ 2 power law (Murakami et al 2001;Takagi-i., Murakami & Koyama 2002), similar to Sgr B2. Therefore, we assume for Sgr C a flux in the MEP energy band which is just scaled with respect to that of Sgr B2 by the same factor which is observed in the soft X-rays, that is, a factor of 3 fainter (Murakami et al 2000).…”
Section: Detectability With Available Technologymentioning
confidence: 99%
“…To calculate the 99 per cent confidence level MDP of the medium/hard X-ray instrument (see Marin et al 2012b Sidoli et al 2001;Terrier et al 2010) being close to the one of the Crab ( ∼ 2), in first approximation we can assume similar fluxes (in mCrab) in the MEP energy band if we neglect absorption below 8 keV. No observation of Sgr C has been made above 10 keV yet, but its soft X-ray continuum has been fitted with a ∼ 2 power law (Murakami et al 2001;Takagi-i., Murakami & Koyama 2002), similar to Sgr B2. Therefore, we assume for Sgr C a flux in the MEP energy band which is just scaled with respect to that of Sgr B2 by the same factor which is observed in the soft X-rays, that is, a factor of 3 fainter (Murakami et al 2000).…”
Section: Detectability With Available Technologymentioning
confidence: 99%
“…A similarly ambiguous situation exists in TC1 (Cernicharo et al 1998) where an outflow is not confirmed. The lack of perfect comparisons is due in part to the following reasons: some possible YSOs have X-ray emission but are not classified because they lack IR counterparts (Takagi et al 2002). In other cases, such as in R Mon, Preibisch et al (2002) showed that the IRS 3 X-ray sources were unlikely to be the outflow source (see also Kohno et al 2002).…”
Section: Ggd 27-xmentioning
confidence: 99%
“…The bubble model has also been used to explain the coherent space velocities of water maser sources from the very source of G (Mac Low & Elitzur 1992), where it was proposed that these sources are from the expanding shells swept by stellar winds. The involvement of cold matter in the hard X-ray emission is strongly inferred by the detection of the fluorescent iron line in Sagittarius B2 and the Arches cluster (Takagi et al 2002;YusefZadeh et al 2002). Because this possibility for the X-ray emission has not been discussed in previous works, we examine this idea here in more detail.…”
Section: Wind-blown Bubblementioning
confidence: 99%